Evidence of niche partitioning among bacteria living on plastics, organic particles and surrounding seawaters. (May 2018) - Dussud, C.; Meistertzheim, A.L.; Conan, P.; Pujo-Pay, M.; George, M.; Fabre, P.; Coudane, J.; Higgs, P.; Elineau, A.; Pedrotti, M.L.; Gorsky, G.; Ghiglione, J.F.
Abstract: Plastic pollution is widespread in ocean ecosystems worldwide, but it is unknown if plastic offers a unique habitat for bacteria compared to communities in the water column and attached to naturally-occurring organic particles. The large set of samples taken during the Tara -Mediterranean expedition revealed for the first time a clear niche partitioning between free-living (FL), organic particle-attached (PA) and the recently introduced plastic marine debris (PMD). Bacterial counts in PMD presented higher cell enrichment factors than generally observed for PA fraction, when compared to FL bacteria in the surrounding waters. Taxonomic diversity was also higher in the PMD communities, where higher evenness indicated a favorable environment for a very large number of species. Cyanobacteria were particularly overrepresented in PMD, together with essential functions for biofilm formation and maturation. The community distinction between the three habitats was consistent across the large-scale sampling in the Western Mediterranean basin. 'Plastic specific bacteria' recovered only on the PMD represented half of the OTUs, thus forming a distinct habitat that should be further considered for understanding microbial biodiversity in changing marine ecosystems. Graphical abstract: Image 1 Highlights: Large-scale study of bacterial life on plastic debris in the Mediterranean Sea. High density of bacteria and patchy organization of biofilm on plastic surfaces. Characterization of 'plastic specific bacteria' compared to surrounding waters. New insights on potential bacterial functions linked with plastic habitat. Abstract : This study is the first description of bacterial abundance and diversity on plastic marine debris (PMD) in the Mediterranean Sea; it describes PMD as a particular habitat for marine bacteria compared to particle-attached and free-living fractions in surrounding waters.